2017
DOI: 10.1093/hmg/ddx414
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of two missense mutations in actin-binding domain 1 of dystrophin associated with Duchenne or Becker muscular dystrophy

Abstract: Missense mutations in the dystrophin protein can cause Duchenne muscular dystrophy (DMD) or Becker muscular dystrophy (BMD) through an undefined pathomechanism. In vitro studies suggest that missense mutations in the N-terminal actin-binding domain (ABD1) cause protein instability, and cultured myoblast studies reveal decreased expression levels that can be restored to wild-type with proteasome inhibitors. To further elucidate the pathophysiology of missense dystrophin in vivo, we generated two transgenic mdx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…The simultaneous induction of ZFAND5 by enhancing the proteasomes' degradative activity should promote the clearance of these ubiquitinated proteins, presumably to promote the efficient clearance of ubiquitinated proteins. Moreover, some forms of Duchenne and Becker muscular dystrophy are due to missense mutations in dystrophin that lead to its rapid degradation by the UPS, and recently down-regulation of ZFAND5 was shown to raise the levels of this critical protein (11). Because down-regulation of ZFAND5 reduced muscle wasting and proteolysis by the UPS, pharmacological antagonists of ZFAND5 might represent a therapy to ameliorate the debilitating loss of muscle protein in various cachectic conditions, as well as in these muscular dystrophies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simultaneous induction of ZFAND5 by enhancing the proteasomes' degradative activity should promote the clearance of these ubiquitinated proteins, presumably to promote the efficient clearance of ubiquitinated proteins. Moreover, some forms of Duchenne and Becker muscular dystrophy are due to missense mutations in dystrophin that lead to its rapid degradation by the UPS, and recently down-regulation of ZFAND5 was shown to raise the levels of this critical protein (11). Because down-regulation of ZFAND5 reduced muscle wasting and proteolysis by the UPS, pharmacological antagonists of ZFAND5 might represent a therapy to ameliorate the debilitating loss of muscle protein in various cachectic conditions, as well as in these muscular dystrophies.…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly suggest ZFAND5's involvement in protein breakdown (9), especially in the accelerated proteolysis responsible for skeletal muscle wasting. Accordingly, downregulation of ZFAND5 (and several other components of the ubiquitin proteasome system) in mouse muscle was recently found to raise the levels of a mutant form of dystrophin found in Duchenne muscular dystrophy (11). In addition, in the macrophage line, RAW264.7, ZFAND5 expression is induced by RANKL, TNFÎą, and IL-1β, and its expression inhibits their differentiation into octeoclasts (12).…”
mentioning
confidence: 99%
“…Each ECC was separated by 3 min of rest to prevent fatigue. The corresponding force drop associated with this protocol for mdx EDL muscle is 85–90% but variations in mechanical parameters across other laboratories can cause force drop from 39% to 90% . The force measured at each ECC was expressed as a percentage of the force produced during the first (“initial”) contraction.…”
Section: Methodsmentioning
confidence: 99%
“…Although it is still under debate, a more than 90% decrease of normal dystrophin levels might have a critical effect on the clinical severity of patients with BMD. Previous studies examined the mechanisms underlying the decrease of tdp427, using in vitro analyses or transgenic mice that overexpress tdp427, and showed that the decreased level of tdp427 was caused by protein degradation following the tertiary instability of the protein ( Henderson et al, 2011 ; McCourt et al, 2015 , 2018 ). However, as patients with BMD exhibit endogenous tdp427 expression under normal promoter activity, such an in vitro or overexpressed tdp427 scenario might not mimic the physiological environment in muscle tissues of patients with BMD.…”
Section: Introductionmentioning
confidence: 99%